Cerebral multifrequency MR elastography by remote excitation of intracranial shear waves - Fehlner, Andreas; Papazoglou, Sebastian; Mcgarry, Matthew D.; Paulsen, Keith D.; Streitberger, Kaspar-Josche; Hirsch, Sebastian; Braun, Juergen; Sack, Ingolf; Guo, Jing (NMR in Biomedicine, 2015)
The aim of this study was to introduce remote wave excitation for high-resolution cerebral multifrequency MR elastography (mMRE). mMRE of 25-45-Hz drive frequencies by head rocker stimulation was compared with mMRE by remote wave excitation based on a thorax mat in 12 healthy volunteers. Maps of the magnitude |G*| and phase ϕ of the complex shear modulus were reconstructed using multifrequency dual elasto-visco (MDEV) inversion. After the scan, the subjects and three operators assessed the comfort and convenience of cerebral mMRE using two methods of stimulating the brain. Images were acquired in a coronal view in order to identify anatomical regions along the spinothalamic pathway. In mMRE by remote actuation, all subjects and operators appreciated an increased comfort and simplified procedural set-up. The resulting strain amplitudes in the brain were sufficiently large to analyze using MDEV inversion, and yielded high-resolution viscoelasticity maps which revealed specific anatomical details of brain mechanical properties: |G*| was lowest in the pons (0.97 ± 0.08 kPa) and decreased within the corticospinal tract in the caudal-cranial direction from the crus cerebri (1.64 ± 0.26 kPa) to the capsula interna (1.29 ± 0.14 kPa). By avoiding onerous mechanical stimulation of the head, remote excitation of intracranial shear waves can be used to measure viscoelastic parameters of the brain with high spatial resolution. Therewith, the new mMRE method is suitable for neuroradiological examinations in the clinic.
CRIS-Team Scopus Importer:2022-08-03
Keywords: Brain; Corticospinal tract; High resolution; In vivo multifrequency MRE; Intracranial shear strain; MR elastography; Pons; Viscoelasticity